(untitled) (International Research Journal of Management and Social Sciences, 2021)
Women have measured a subject class due to which the incidents of violence i.e. acid throwing, domestic violence, honor killings, structural violence, bride burning (suicide), and gender discrimination against them are common practice in the world but especially in the subcontinent. In Islam, there is no gender discrimination, but despite clear Islamic injunctions, women are being deprived of their basic human rights i.e. education, etc. Due to these Women in the country are facing social, cultural, financial, and psychological tribulations. The government is examining the plight of women like redundant spectators and has not taken necessary remedial measures i.e. increase in women's literacy rate and economic independence to find pragmatic solutions to end the felon behavior. The study will cover personal feelings about gender-based oppression of male counterparts and violations of religion, customs, and traditions. https://doi.org/10.5281/zenodo.10347624